Marketing approach to amusement park business - Tkachuk (Stakhurska), Svitlana; Stahurska, Svitlana (My University, 2016)
The paper examines marketing specificities of entertainment industry in example of amusement park. The entertainment industry is considered to be related to the service sector, the sector of non-material production with all the particular qualities of it's, such as impalpability, variability, inseparability from the source and inability for storage. The services of amusement park are regarded as the variety of specific services, which may be designed for different types of consumers.In order to this fact it is proposed the segmentation approach for customers of amusement park services. In basis of the segmentation is the emotional criteria, that considers the classification of emotions by B. Dоdonov and other classifications. In accordance to the market segments the types of amusement services as the strategic business units are proposed, including such elements of marketing-mix as product, process and physical evidence. Element "product" is considered to be in combination with element "process" for the specific essence of service product, which combines instrumental and functional quality. It is also considered, that consumer buys the service of amusement park not for the determined material result, but for the process. The process is viewed as the result of the service consumption. The result and the process are measured by the emotions, for which consumer buys the amusement service.
Keywords: marketing; entertainment industry; marketing of amusement park; marketing of service sector; market segmentation; customers' emotions; romantic emotions; emotions of fear; esthetic emotions; hedonistic emotions; маркетинг; сфера розваг; маркетинг парку розваг; маркетинг сфери послуг; маркетингова сегментація; емоції споживачів; романтичні емоції; емоції страху; естетичні емоції; гедоністичні емоції; сфера развлечений; маркетинг парка развлечений; маркетинг сферы услуг; маркетинговая сегментация; эмоции потребителей; романтические эмоции; эмоции страха; эстетические эмоции; гедонистические эмоции; кафедра маркетингу; кафедра економіки праці та менеджменту